New methods, reflections and applications domains in transport appraisal - Mouter, Niek (Advances in transport policy and planning, 2021)
New Methods, Reflections and Application Domains in Transport Appraisal, Volume 7 in the Advances in Transport Policy and Planning series, assesses both successful and unsuccessful practices and policies from around the world. Chapters in this new release include Evaluating transport equity, Participatory Value Evaluation, Sustainability assessment of transport policies, plans and projects, Deliberative appraisal methods, Appraisal methods of public transport projects, Appraisal of cycling and pedestrian projects, Appraisal of Freight Project, Project appraisal methods: tools for optimizing or for informed political debate?, and Research agenda for appraisal methods.